Information technology and the US productivity revival: What do the industry data say? - Kevin J. Stiroh (Federal Reserve Bank of New York, 2001)
This paper examines the link between information technology (IT) and the U.S. productivity revival in the late 1990s. Industry-level data show a broad productivity resurgence that reflects both the production and the use of IT. The most IT-intensive industries experienced significantly larger productivity gains than other industries and a wide variety of econometric tests show a strong correlation between IT capital accumulation and labor productivity. To quantify the aggregate impact of IT-use and IT-production, a novel decomposition of aggregate labor productivity is presented. Results show that virtually all of the aggregate productivity acceleration can be traced to the industries that either produce IT or use IT most intensively, with essentially no contribution from the remaining industries that are less involved in the IT revolution.
Keywords: 330; Information technology; Industrial productivity; Labor productivity; Informationstechnik; Produktivität; Arbeitsproduktivität; USA